Brigands & breadknives [large type] - Baldree, Travis, 1977- (Baldree, Travis, 1977- Legends & lattes (Series), 2026)
"Return to the cozy fantasy world of the #1 New York Times bestselling Legends & Lattes series with a new adventure featuring fan-favorite, foul-mouthed bookseller Fern. Fern has weathered the stillness and storms of a bookseller's life for decades, but now, in the face of crippling ennui, transplants herself to the city of Thune to hang out her shingle beside a long-absent friend's coffee shop. What could be a better pairing? Surely a charming renovation montage will cure what ails her! If only things were so simple... It turns out that fixing your life isn't a one-time prospect, nor as easy as a change of scenery and a lick of paint. A drunken and desperate night sees the rattkin waking far from home in the company of a legendary warrior, an imprisoned chaos-goblin with a fondness for silverware, and an absolutely thumping hangover. As together they fend off a rogue's gallery of ne'er-do-wells trying to claim the bounty the goblin represents, Fern may finally reconnect with the person she actually is when nothing seems inevitable."--